Expertise on the feather plucking of live geese - Kozák, János (Animal welfare, Ethology and Housing Systems (AWETH), 2009)
The goose feather is such a renewable raw material resource, which exceeds other textile filling materials in many properties. Using the feather and down goes back high in the past. Harvesting feather from live geese is based on moulting, which is a genetically fixed feather change and feathering process. With selection works and proper keeping systems the man developed a new domestic animal property, the increased feather producing ability. The correct feather collecting in the right time doesn’t distress the geese, doesn’t have any detrimental effect on their state of health, and doesn’t have any adverse influence on their welfare.
Keywords: goose feather; feather collecting; state of health; welfare